2002
DOI: 10.1073/pnas.261708798
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency and iron excess damage mitochondria and mitochondrial DNA in rats

Abstract: Approximately two billion people, mainly women and children, are iron deficient. Two studies examined the effects of iron deficiency and supplementation on rats. In study 1, mitochondrial functional parameters and mitochondrial DNA (mtDNA) damage were assayed in iron-deficient (<5 g͞day) and iron-normal (800 g͞day) rats and in both groups after daily high-iron supplementation (8,000 g͞day) for 34 days. This dose is equivalent to the daily dose commonly given to iron-deficient humans. Iron-deficient rats had lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
190
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(202 citation statements)
references
References 50 publications
11
190
0
1
Order By: Relevance
“…This finding is consistent with the study of Walter et al [7], who demonstrated that both iron overload and iron deficiency were detrimental for the functioning of liver mitochondria [7]. It is well known that iron excess deranges the energy metabolism of tissues and constitutes a bad prognosis in patients with cardiac disorders.…”
Section: Hampsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with the study of Walter et al [7], who demonstrated that both iron overload and iron deficiency were detrimental for the functioning of liver mitochondria [7]. It is well known that iron excess deranges the energy metabolism of tissues and constitutes a bad prognosis in patients with cardiac disorders.…”
Section: Hampsupporting
confidence: 92%
“…Moreover, it constitutes the main component of cofactors not only for abundant globins responsible for oxygen transport and storage (haemoglobin, myoglobin), but also for numerous enzymes of the oxidative metabolism and mitochondrial functioning [2,4,6]. The particular importance of optimal iron status is well reflected by the fact that both intracellular iron excess and depletion impair the functioning of mitochondria, leading to excessive oxidative stress and deranged energy metabolism [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For IRP1, which is a bifunctional protein, iron inhibits RNAbinding activity by promoting assembly of an iron-sulfur cluster in the binding protein, thereby converting it to cytosolic aconitase [42] . Walter et al [43] has suggested that iron deficiency can induce the IRP-mediated cellular iron signaling pathway, which leads to enhanced intracellular iron levels. Therefore, we assessed the activity of cytosolic and mitochondrial aconitase.…”
Section: Discussionmentioning
confidence: 99%
“…Its catalytic role depends on the ability of ferrous (Fe 2ϩ ) and ferric (Fe 3ϩ ) iron to respectively donate and accept electrons under conditions prevailing in biological systems. However, iron also promotes the formation of reactive oxygen species that can damage DNA, proteins, and lipids within cells (1,2). Multiple mechanisms have evolved to chaperone iron and to regulate its concentrations through the coordinated modulation of transport, storage, and iron utilization so that adequate iron is available for physiological functions with tolerable toxicity.…”
mentioning
confidence: 99%